HUBUNGAN GAYA KEPEMIMPINAN DAN KINERJA DENGAN ETOS KERJA GURU SEKOLAH DASAR DI KOTA PADANG PANJANG - Hubban Jamma (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
Relations Leadership Style and Performance with the Work Ethic Teachers in Primary School Kota Padangpanjang. The purpose of this research was to reveal how extend the correlations of principal leadership, teachers’ work satisfaction with teachers’ work ethic at elementary schools in Padang Panjang Regency.This research revealed: (1) Style of Principal leadership correlated with teachers’ work ethic significantly. The extended of correlation of teachers work ethic was determined by style of principal leadership as 27,1 %. (2) Teachers work satisfaction correlated with teachers’ work ethic significantly. Teachers’ work ethic was determined by teachers work satisfaction as 26,2 %. (3) The style of principal leadership and teachers work satisfaction (X2) correlated significantly with teachers’ work ethic at elementary schools in Padang Panjang Regency, and the extend teachers’ work ethic was determined by style of principal eldership and teachers’ work satisfaction as 39,5 %.Kata kunci:  Gaya kepemimpinan, kepuasan kerja, etos kerja